Yield and financial analysis of an agroforestry system with coffee (Coffea arabica cv caturra) and poro (Erythrina poeppigiana) under different densities of laurel (Cordia alliodora) - Hernández Guerra, Oscar R. (1995)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1995